Michel de Montaigne and the Power of Language - Poštić, Svetozar (Verbum, 2015)
This essay argues that the main instrument Montaigne, 16th-century French thinker and writer, used for creating a “new ontology,” as Nicola Panichi calls it (2004, 278), was language and a special style of writing. He, first of all, created – or revived from the Antiquity – a new genre most suitable for a new discourse, and christened it essai. Then he applied a method known in humanist schools of the Renaissance as ultraquem partem to relativise all previous thought. Finally, he employed a thorough, frank examination of his own behaviour, habits and preferences, adorned with Latin sentences, to promote self-analysis as a path to personal contentment. This article applies the theory of Bakhtin, a 20th-century Russian philosopher and sociolinguist, especially his essay “Discourse in the Novel” (“Слово в романе”), in the analysis of the peculiarity of Montaigne’s composition and its purposefulness in expressing at that time dangerous, but already prevalent worldview. Since battling medieval Christian thought was the paramount assignment of his endeavour, the quotes are mostly taken from Montaigne’s only essay – and by far the longest in the three-volume collection – entirely dedicated to religion, “Apologie de Raimond Sebond.”
Keywords: Montaigne; language; Bakhtin; discourse; essay